El campo literario post-15-M desde una perspectiva feminista - Isabelle Touton (Cahiers de Civilisation Espagnole Contemporaine)
This article aims to study how the post-15-M literary field has been modified by feminism, after demonstrating the intertwining of the current thrust of the feminist movement in Spain and that of the 15-M movement. It highlights in particular the presence of feminist thought, from vulnerability, the rejection of authority, the embodied self and the fight to be heard in often hybrid texts that navigate between essay, (self-)fiction, journalism and non-fiction.